Representation and investigation of solutions of a nonlocal boundary-value problem for a system of partial differential equations - Il'kiv, V. S.; Ptashnik, B. I. (Ukrains’kyi Matematychnyi Zhurnal, 1996)
We study the boundary-value problem for a system of partial differential equations with constant coefficients with conditions nonlocal in time. By using a metric approach, we prove the well-posedness of the problem in the scale of Sobolev spaces of functions periodic in space variables. By using matrix calculus, we construct an explicit representation of a solution.